EFFECT OF ACCELERATED AGING ON VIGOR OF LOCAL MAIZE SEEDS IN TERM OF ELECTRICAL CONDUCTIVITY AND RELATIVE GROWTH RATE (RGR). - Hussein, Hussein; Shaheed, Abdulla; Yasser, Oda (Iraqi Journal of Science, 2024)
Maize (Zea mays L.) seeds were subjected to accelerated aging treatment for, 3,7, and 14 days at 45 ±1 C° and 100% relative humidity. These artificially aged seedswere compared to control (Unaged seeds) for evaluation of vigor in seeds.Accelerated aging of Maize seeds up to three days had significant effect ongermination percentage & solute leakage. However, further increase in aging periodcaused an increased in solute leakage and a decrease in germination percentage.Germinability was lost completely at 14 days of accelerated aging. In addition, thereduction in germination percentage was correlated with decrease in seedling length,germination speed index, seed vigor index, seedling fresh & dry weight. Finally, theresults revealed that accelerated aging caused depression of maize seeds viabilitythrough the above parameters.